Indonesian’s Natural Gas: Production, Reserves, and Challenges - Widarsono, Bambang (UI Scholars Hub, 2007)
In the last few years it has occurred the decreasing of Indonesia’s oil production in national scale in 10% per year. At the same time the situation of the national gas showing the increasing of the production and the backup. The production rate can be maintained and the backup even can show the growth from year to year. The analysis of the history of the production and the backup, exploration activity, and the comparison between the discovery of the oil and gas in the recent years underlying that the oil can be the sources of energy and the income for the state. Even will facing some challenge in oil exploitation in the term of the application of technology, infrastructure, law enforcement, social unrest, strict regulation, and incentives. That challenge must be overcome if the gas production, and also oil, to achieve the sustainable.